1996
DOI: 10.1007/bf01411289
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of the anterior cerebral artery after gamma knife irradiation in a rat

Abstract: The anterior cerebral artery of rats was irradiated at the level of the circle of Willis by Gamma Knife with a maximum dose of 25, 50, or 100 Gy. Occlusion of the anterior cerebral artery was observed in one rat which was followed for 20 months after irradiation of 100 Gy. Cerebral infarction was found at the midline-frontal region and the cingulate gyrus. Arterial wall thickening with fibrosis, splitting of the internal elastic membrane, luminal organized thrombus, and migration of smooth muscle cells into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…58 Available data regarding the biology of radiation-induced vascular obliteration result from observations in BAVM tissue resected after radiosurgical treatment 14,82 and in irradiated arteries in animal models. 8,49,70,77 Observations from BAVM tissue 14,82 have suggested that damaged endothelial cells shrink, detach from neighboring endothelial cells and basement membrane, and permit platelet infiltration with deposition of fibrin and hyaline. As these endothelial cells slough off over time, inhibition of smooth muscle cell proliferation is lost, and smooth muscle cell migration into the subintimal layer results in collagen deposition that thickens the subintima and adventitia, progressively narrowing the lumen and eventually occluding it.…”
Section: Stereotactic Radiosurgery and Radiobiology Of Bavmsmentioning
confidence: 99%
See 2 more Smart Citations
“…58 Available data regarding the biology of radiation-induced vascular obliteration result from observations in BAVM tissue resected after radiosurgical treatment 14,82 and in irradiated arteries in animal models. 8,49,70,77 Observations from BAVM tissue 14,82 have suggested that damaged endothelial cells shrink, detach from neighboring endothelial cells and basement membrane, and permit platelet infiltration with deposition of fibrin and hyaline. As these endothelial cells slough off over time, inhibition of smooth muscle cell proliferation is lost, and smooth muscle cell migration into the subintimal layer results in collagen deposition that thickens the subintima and adventitia, progressively narrowing the lumen and eventually occluding it.…”
Section: Stereotactic Radiosurgery and Radiobiology Of Bavmsmentioning
confidence: 99%
“…8,49,58,70,77 Failed mitosis of irradiated endothelial cells, damaged by direct interactions with irradiating electrons and indirect free-radical byproducts, results in eventual apoptosis 26 and initiation of radiationinduced arteriopathy. As such, it is believed that the latency period of BAVM obliteration after SRS is dependent on the turnover rate of endothelial cells, which typically ranges on the order of a couple of months to a couple of years, since initiation of the arteriopathy only manifests once endothelial cells attempt mitosis.…”
Section: Stereotactic Radiosurgery and Radiobiology Of Bavmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of the effects of radiosurgery on normal vessels include a study of GKS on cat basilar artery 10 and on rat anterior cerebral artery. 5 Findings included intimal proliferation but no vessel occlusion except in 1 rat anterior cerebral artery 20 months after treatment with 100 Gy.…”
Section: Discussionmentioning
confidence: 96%
“…The comparatively deleterious effects of radiation doses of up to a few hectograys delivered to arteries in the broad-beam mode have been described (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%